Biological fluids at crime scenes: Identification methods and forensic applications – A narrative review (Research, Society and Development, 2025)
In this context, the present study aims, through a literature review, to gather and examine the main types of biological fluids — blood, semen, and saliva — in forensic contexts, as well as the most effective biochemical and molecular methods in order to recognize their respective applications in the investigative process, in addition to the challenges and barriers related to this stage. The work was developed based on the analysis of scientific publications, addressing validated methods widely employed in forensic routines. Among them, preliminary tests such as the use of luminol and confirmatory tests that correctly allow the verification of DNA through genetic amplification techniques stand out. The applications of these analyses in the field of criminal investigation were also discussed, highlighting the use of genetic profile databases from the Department of Technical-Scientific Police (DPTC), as well as challenges such as sample contamination, biological material degradation, and the preservation of the chain of custody. Thus, the study highlights the significance of blood, semen, and saliva in the elucidation of crimes, in the reconstruction of the dynamics of events, and in strengthening the evidence presented in court.